Interpreting Surface Degradation of HTV Silicone Rubber Filled with Micro/Nano-Silica Under AC and DC Voltages - Akbar, Muhammad; Ullah, Rahmat; Abdul Karim, M. R. (Journal of electronic materials, 2020)
In this study, high-temperature vulcanized silicone rubber filled with different concentrations of micro- and nano-sized silica were tested under synergistic exposure to multi-stress conditions for a time period of 5000 h separately under alternating current and direct current voltages. Different characterization methods were used to evaluate the degradation performance. After each aging cycle, leakage current was measured and hydrophobicity classifications were determined by using contact angle measurement and amethod proposed by the Swedish Transmission Research Institute. Scanning electron microscopic study and Fourier transform infrared spectroscopy were performed for each test sample. Mechanical performance was assessed by measuring hardness, tensile strength and elongation-at-break. An outcome of this investigation revealed that samples stressed with DC voltage experienced 20–30% degradation compared to AC-stressed samples under common environmental stresses. All hybrid composites were found more resistant to aging but to a different degree depending on the composition. The test sample designated as TS2 was found to offer the highest resistance to aging.